Quality Analysis of Multimedia Teaching in Vocal Music Class Combining Elitist Teaching-Learning-Based Optimization Algorithm. (2nd August 2021) - Yang, Hongcai
Abstract : With the social and economic development, there have been more and more abundant multimedia carriers. In this paper, based on the elitist teaching-learning-based optimization algorithm, the factors that affect the quality of teaching are analyzed mainly from the perspective of teachers in terms of the teaching philosophy, the design level of informatization teaching, the application of new teaching models, the evaluation of teaching effects, and other aspects. The quality of multimedia teaching in vocal music class is analyzed, aiming to improve the quality of teaching. The results of this study indicate that the proposed algorithm is effective.